Exploring microRNA targeting as a promising approach for solid tumor treatment - Shademan, Behrouz; Karamad, Vahidreza; Nourazarian, Alireza; Biray Avci, Cigir (Frontiers in Oncology, 2025)
The discovery of microRNAs (miRNAs) and their pivotal role in gene regulation has opened up new avenues for innovative cancer treatments. Recent years have witnessed extensive research into the intricate mechanisms of miRNAs and their impact on solid tumors. These small non-coding RNA molecules are central to gene regulation and are frequently dysregulated in various cancers, particularly solid tumors. Dysregulation of specific miRNAs can initiate, progress, and metastasize tumors, making them appealing targets in cancer therapy. This article explores recent studies on identifying specific miRNAs associated with solid tumors and their influence on crucial signaling pathways. These findings enable precise targeting of cancer cells, reducing damage to healthy tissues and minimizing side effects commonly associated with conventional cancer treatments. Understanding the complex regulatory networks governed by miRNAs allows researchers and clinicians to develop highly effective, personalized treatment strategies, heralding a new era of tailored cancer medicine. Ongoing research in this field holds immense promise for pioneering targeted therapies that can significantly improve outcomes and the quality of life for individuals battling solid tumors.